2015
DOI: 10.1155/2015/378627
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Quadrilateral Space Block for the Diagnosis of Quadrilateral Syndrome

Abstract: Quadrilateral space syndrome (QSS) is a rare nerve entrapment disorder that occurs when the axillary nerve and posterior circumflex humeral artery (PCHA) become compressed in the quadrilateral space. QSS presents as vague posterolateral shoulder pain that is exacerbated upon the abduction and external rotation of the shoulder. Diagnosis of QSS is difficult because of the vague presentation of QSS. In addition, even though MRI and MR angiography can be used in QSS diagnosis, there is currently no “gold standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Arteriography of upper limb is also of high diagnostic value for the diagnosis of pressure in PCA. Although it had been reported in the literature that the specificity of QSS diagnosis by arterial angiography arteriography is relatively low, [ 14 , 15 ] EMG can detect latency and amplitude of axillary nerve to determine the degree of nerve damage, and can detect denervation potential of the muscles around the quadrilateral space. [ 16 , 17 ] However, in a study of EMG detection of axillary nerve in QSS showed high false-negative rates.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriography of upper limb is also of high diagnostic value for the diagnosis of pressure in PCA. Although it had been reported in the literature that the specificity of QSS diagnosis by arterial angiography arteriography is relatively low, [ 14 , 15 ] EMG can detect latency and amplitude of axillary nerve to determine the degree of nerve damage, and can detect denervation potential of the muscles around the quadrilateral space. [ 16 , 17 ] However, in a study of EMG detection of axillary nerve in QSS showed high false-negative rates.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-two bodies donated to science [all Caucasian type; 21 male, 25 female; 68 (standard deviation, 14) kg, 167 (9) cm, 79 (11) yr], which were donated to the Department of Anatomy of the Medical University Graz, were investigated. They were under the approval and the strict rules of the Anatomical Donation Program of the University of Graz and according to Austrian law.…”
Section: Methodsmentioning
confidence: 99%
“…Digital subtraction angiography, computed tomography angiography, and magnetic resonance angiography have all been used to visualize PHCA occlusion [ 2 , 31 ]. While there is no “gold standard” diagnostic test for QSS, magnetic resonance imaging (MRI) is typically the first choice of imaging [ 32 ]. MRI often demonstrates focal fatty atrophy of the teres minor muscle and can exclude pathological causes of shoulder pain ( Figure 2 ) [ 1 , 7 , 32 ].…”
Section: Presentation Differential Diagnoses Imaging and Other mentioning
confidence: 99%
“…While there is no “gold standard” diagnostic test for QSS, magnetic resonance imaging (MRI) is typically the first choice of imaging [ 32 ]. MRI often demonstrates focal fatty atrophy of the teres minor muscle and can exclude pathological causes of shoulder pain ( Figure 2 ) [ 1 , 7 , 32 ]. Arteriography has been described as the cornerstone of diagnosis in QSS; it is used to reveal compression of the PHCA while the patient’s arm is in abduction and external rotation [ 3 ] ( Figure 3 ).…”
Section: Presentation Differential Diagnoses Imaging and Other mentioning
confidence: 99%